Insights into the divergence of the photosynthetic LH1 complex obtained from structural analysis of the unusual photocomplexes of Roseospirillum parvum - Xiang-Ping Wang; Guang-Lei Wang; Yuan Fu; Akane Minamino; Mei-Juan Zou; Fei Ma; Bo Xu; Zheng-Yu Wang-Otomo; Yukihiro Kimura; Michael T. Madigan; Jörg Overmann; Long-Jiang Yu (Communications Biology)
Abstract Purple phototrophic bacteria produce two kinds of light-harvesting complexes that function to capture and transmit solar energy: the core antenna (LH1) and the peripheral antenna (LH2). The apoproteins of these antennas, encoded respectively by the genes pufBA and pucBA within and outside the photosynthetic gene cluster, respectively, exhibit conserved amino acid sequences and structural topologies suggesting they were derived from a shared ancestor. Here we present the structures of two photosynthetic complexes from Roseospirillum (Rss.) parvum 930I: an LH1–RC complex and a variant of the LH1 complex also encoded by pufBA that we designate as LH1′. The LH1–RC complex forms a closed elliptical structure consisting of 16 pairs of αβ-polypeptides that surrounds the RC. By contrast, the LH1′ complex is a closed ring structure composed of 14 pairs of αβ-polypeptides, and it shows significant similarities to LH2 complexes both spectrally and structurally. Although LH2-like, the LH1′ complex is larger than any known LH2 complexes, and genomic analyses of Rss. parvum revealed the absence of pucBA, genes that encode classical LH2 complexes. Characterization of the unique Rss. parvum photocomplexes not only underscores the diversity of such structures but also sheds new light on the evolution of light-harvesting complexes from phototrophic bacteria.